Deskripsi Metadata dalam Manajemen Data Penelitian: Studi Kasus pada Sistem Repositori Ilmiah Nasional - Seno Yudhanto; Nina Mayesti (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
Organizing research data is very important for data and information managers through a research data management mechanism (research data management/MDP) in a repository system. In this mechanism, research data must be organized and described as an effort to provide access. One important aspect of organizing is the availability of metadata. This Study was supported by the Institute of Sciences of Indonesia (LIPI) and the SAINTEK Scholarship from the Ministry of Research and Technology/National Research and Innovation Agency of the Republic of Indonesia (KEMENRISTEK/BRIN) in 2020 and it’s purpose is to identify and describe metadata standards and metadata elements used in research data management in the National Scientific Repository (RIN) system. This study uses a qualitative approach with a case study method. Sources of data come from literature / document studies and direct observation. The results of the study show that the RIN system adopts descriptive metadata from three main standards, they are DublinCore, DataCite, and DDI. As a medium for describing research data in general, the metadata sections provided by the RIN system in the dataset folder are quite large and complete. Of the 35 metadata fields available in the dataset folder in this system, the three metadata standards complement each other with an adaptation of the dominant DDI standard with 32 metadata fields. However, the fields that are available can also be found in other standards, such as the title, subject, or keyword fields that are also found in the DublinCore and DataCite standards. Thus, the metadata fields provided in the RIN system is good enough and sufficient for research data management needs.